Building material as well as preparation method and application thereof

Tobemullite is generated through the hydrothermal reaction between polycrystalline silicon waste residue powder and chromium residue powder and quicklime, which solves the problems of high preparation cost and low resource utilization rate of tobemullite, and realizes low-cost Tobemullite Prepare and chromium ion cure to achieve high compressive strength and low water absorption performance.

CN119263676APending Publication Date: 2025-01-07HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478554.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, the preparation cost of toberymicrostone building materials is high, and the treatment efficiency of polysilicon waste slag and chromium slag is low, resulting in waste of resources and environmental pollution.

Method used

By hydrothermal reaction between polycrystalline silicon waste slag powder and chromium slag powder and quicklime in water, to produce tobemollite, and chromium ions are cured in the process, reducing material costs and achieving comprehensive utilization of resources.

Benefits of technology

The low-cost preparation of toberomalite has been achieved, the utilization rate of polycrystalline silicon waste slag and chromium slag has been improved, and the environmental pollution problem has been solved. The prepared wall tiles have high compressive strength and low water absorption rate, meeting the national standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263676A_ABST
    Figure CN119263676A_ABST
Patent Text Reader

Abstract

The invention relates to a building material and a preparation method and application thereof, and belongs to the technical field of building materials. The preparation method of the building material comprises the following steps: carrying out hydrothermal reaction on a mixture composed of polycrystalline silicon waste residue powder, chromium residue powder and quick lime in water; in the mixture, the molar ratio of the calcium element to the silicon element is (1.0-1.15): 1. According to the preparation method of the building material, the polycrystalline silicon waste residue powder and the chromium residue powder are subjected to the hydrothermal reaction with the quick lime in the water, the polycrystalline silicon waste residue powder can be converted into tobermorite, meanwhile, the tobermorite can be used for solidifying chromium ions in the chromium residue powder, the manufacturing cost of the tobermorite building material is reduced, and the building material has the advantages of being environmentally friendly and free of pollution. And the comprehensive utilization of the polycrystalline silicon waste residue powder and the chromium residue powder is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a building material and a preparation method and application thereof, belonging to the technical field of building materials. Background Art

[0002] After chromite is used to produce chromium salt products, a large amount of chromium slag will be produced. For every 1.0t of chromium salt products produced, about 0.8t of chromium slag will be produced. In terms of weight percentage, the main components of chromium slag are: 20% to 25% Al 2 O 3 , 5% to 10% CaO, 2% to 5% SiO 2 , 30%~35%Fe 2 O 3 、30%~35%Cr 2 O 3 and 5% to 8% MgO. Chromium slag is a solid hazardous waste, showing strong toxicity and carcinogenicity. If the chromium slag is discharged directly without any treatment, it will seriously pollute the environment and pose a great threat to human health. At present, the treatment of chromium slag is divided into wet detoxification and reduction detoxification. The wet detoxification is to ball mill the chromium slag, soak it in acid solution, and then 6+ Transferred to solution, this method reduces Cr 6+ The treatment effect is not stable. The reduction detoxification method can make Cr 6+ Reduction to Cr 3+ , effectively reducing the toxicity of the Cr-containing system. However, in the application process, in order to achieve a good detoxification effect, the amount of reducing agent used often far exceeds the Cr content in the Cr-containing system, resulting in excessively high treatment costs.

[0003] Polysilicon waste residue is industrial solid waste generated during the production of polysilicon slices. In terms of weight percentage, polysilicon waste residue is mainly composed of: 65% to 70% SiO 2 8% to 10% Al 2 O 3 4% to 6% Fe 2 O 3 , 10% to 15% CaO and 1% to 2% MgO. At present, a large amount of polysilicon waste residue is not effectively utilized, but simply landfilled or composted, which not only occupies a large amount of land, but also causes serious pollution. At present, the treatment of polysilicon slag relies on hydrolysis technology, but this technology has problems such as slow treatment efficiency and insufficient resource recovery in specific applications.

[0004] Tobermorite is a kind of calcium silicate hydration product, with the characteristics of small bulk density, low thermal conductivity, high temperature resistance and high strength. It has been widely used in kilns, equipment and pipeline reaction engineering in metallurgy, building materials, electricity, chemical industry and other industries. It is an important inorganic non-metallic material. Tobermorite plays an important role in the stability of heavy metals. At the same time, its excellent ion exchange performance can solidify Pb 2+ , Cu 2+ Cr 3+ and Ni 2+ Heavy metal ions such as quartz and zirconium are used as raw materials. Since tobermorite has a large demand when used as a building material, and the building material field does not have high requirements for raw materials. Therefore, tobermorite after solidification of heavy metal ions can still be used as a building material. At present, when preparing tobermorite, quartz powder, diatomaceous earth, zeolite, bentonite, zirconium silicon slag, etc. are usually used as siliceous raw materials, which has the disadvantage of high cost. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a building material, which can solve the problem of high cost in the current preparation of tobermorite building materials.

[0006] The second object of the present invention is to provide a building material that can solve the problem of high preparation cost of current tobermorite building materials.

[0007] The third object of the present invention is to provide an application of a building material in the preparation of wall tiles, which can solve the problem of high cost in the preparation of wall tiles using tobermorite building materials.

[0008] In order to achieve the above-mentioned object, the technical solution adopted by the method for preparing the building material of the present invention is:

[0009] A method for preparing building materials comprises the following steps: subjecting a mixture consisting of polysilicon waste slag powder, chromium slag powder and quicklime to a hydrothermal reaction in water; in the mixture, the molar ratio of calcium element to silicon element is (1.0-1.15):1.

[0010] The preparation method of the building material of the present invention comprises the following steps: subjecting polysilicon waste slag powder and chromium slag powder to a hydrothermal reaction with quicklime in water, so that the polysilicon waste slag powder can be converted into tobermorite, and the tobermorite can be used to solidify chromium ions in the chromium slag powder, thereby not only reducing the manufacturing cost of the tobermorite building material, but also realizing the comprehensive utilization of the polysilicon waste slag powder and the chromium slag powder.

[0011] Preferably, the polysilicon waste slag powder is composed of the following components in mass fractions: 65% to 70% SiO 2 , 8% to 10% Al 2 O 3 4% to 6% Fe 2O 3 , 10%~15% CaO and 1%~2% MgO.

[0012] Preferably, the chromium slag powder is composed of the following components by mass fraction: 20% to 25% Al 2 O 3 , 5% to 10% CaO, 2% to 5% SiO 2 , 30%~35%Fe 2 O 3 、30%~35%Cr 2 O 3 And 5% to 8% MgO.

[0013] Preferably, in the mixture, the mass fraction of polysilicon waste slag powder is 40-45%, the mass fraction of chromium slag powder is 30-35%, and the mass fraction of quicklime is 20-25%.

[0014] Preferably, the temperature of the hydrothermal reaction is 200-230° C., the time is 1-10 h, and the pressure is 0.7-1.0 MPa; the mass ratio of the mixture to water is 1:(22-25).

[0015] Preferably, the temperature of the hydrothermal reaction is 205-230° C., the time is 1-10 h, and the pressure is 0.8-1.0 MPa; the mass ratio of the mixture to water is 1:(24-25).

[0016] Preferably, the particle size of the polysilicon waste slag powder is greater than 200 mesh; the particle size of the chromium slag powder is greater than 200 mesh.

[0017] Preferably, in the mixture, the molar ratio of calcium to silicon is (1.02-1.14):1; in the mixture, the mass fraction of polysilicon waste slag powder is 40-45%, the mass fraction of chromium slag powder is 33-35%, and the mass fraction of quicklime is 21-25%; the polysilicon waste slag powder is composed of the following components by mass fraction: 67%-70% SiO 2 8% to 10% Al 2 O 3 , 5% to 6% Fe 2 O 3 , 15% CaO and 2% MgO; the chromium slag powder consists of the following components by mass fraction: 20% Al 2 O 3 , 8% to 10% CaO, 2% to 5% SiO 2 30% to 31% Fe 2 O 3 30%~32%Cr 2 O 3 And 5% to 8% MgO.

[0018] The technical solution adopted by the building material of the present invention is:

[0019] A building material prepared by the method for preparing the building material as described above.

[0020] The building material of the present invention is prepared by hydrothermal reaction of polysilicon waste slag powder and chromium slag powder with quicklime in water, and has the advantage of low cost. The building material of the present invention is tobermorite with fixed chromium ions, and has the structure and performance of tobermorite.

[0021] The technical solution adopted by the application of the building material of the present invention in the preparation of wall bricks is:

[0022] A use of the building material as described above in preparing wall tiles.

[0023] The building material of the invention is used to prepare wall tiles, which can reduce the cost of raw materials. At the same time, the prepared wall tiles have a compressive strength of up to 18MPa, a water absorption rate of less than 10%, and a softening coefficient of up to 1.0, reaching the MU15 grade wall tile standard in the national standard JC / T422-2007. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the EDS spectrum of the building material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The preparation method of the building material of the present invention is a pioneering invention. Based on the problem of high cost in the current preparation method of tobermorite, the present invention utilizes polysilicon waste slag as the siliceous raw material for synthesizing tobermorite, and simultaneously utilizes tobermorite to solidify chromium ions in chromium slag during the hydrothermal reaction process, which not only solves the problem of the shortage of siliceous raw materials for synthesizing tobermorite, but also solves the problem of large-scale accumulation of polysilicon waste slag and chromium slag to pollute the environment, thus achieving the goal of "turning waste into treasure and treating waste with waste".

[0026] The principle of the preparation method of the building material of the present invention is as follows: During the hydrothermal reaction, Ca(OH) 2 Amorphous SiO in polysilicon waste 2 The reaction gradually transforms into CSH gel; as the reaction continues, it gradually and completely transforms into amorphous CSH gel. At the same time, under high temperature and high pressure conditions, the CSH gel gradually transforms into a tobermorite ore phase with higher crystallinity; finally, the CSH gel completely transforms into tobermorite. The reaction occurring under hydrothermal conditions is shown in the following formula:

[0027] 5CaO+6SiO 2 +5H 2 O=5CaO·6SiO2 ·5H 2 O

[0028] The tobermorite in the building material prepared by the invention has a layered structure containing two layers of silicon tetrahedrons with calcium oxygen octahedron as the center, and water molecules and calcium ions are contained between the layers.

[0029] Due to Cr 3+ Radius ratio Ca 2+ Small, in the six-fold coordination of tobermorite, Cr 3+ Easy to replace Ca 2+ Enter the tobermorite structure, forming a stable Cr-O ionic bond or occupying the Ca 2+ The Cr-OH bond is formed with the hydroxyl group of water molecules, which will not cause the deformation of the tobermorite structure. 6+ It can replace the water molecules of tobermorite and enter the interlayer, and interact with Ca 2+ Formation of stable CaCrO 4 Tobermorite can solidify Cr in chromium slag 3+ and Cr 6+ At the same time, the structure and properties of tobermorite are not affected.

[0030] The beneficial effects of the present invention are as follows: (1) Microwave hydrothermal reaction can heat the inside and outside of the material uniformly at the same time, so that the polar molecules of the reaction system produce high-frequency rotation, and the substances that are difficult to dissolve or insoluble under conventional hydrothermal reaction conditions are dissolved and recrystallized under high temperature and high pressure reaction conditions, thereby accelerating the synthesis speed, and the synthesis time is a few or several tenths of that of the traditional heating method. Therefore, the use of microwave hydrothermal reaction can accelerate the reaction speed, shorten the synthesis time, and reduce production energy consumption.

[0031] (2) In the present invention, the solid waste utilization rate of polysilicon waste slag and chromium slag can reach up to 90% at most, and the solid waste is recycled and recycled, which completely solves the pollution problem of chromium slag and turns it into a real secondary resource. At the same time, it can also save resources and protect the environment, and promote the green, healthy and sustainable development of the chemical industry.

[0032] (3) When the green building material (containing chromium tobermorite) prepared by the present invention is used to prepare wall tiles, the hydrogrossular garnet and hydrated calcium silicate gel generated in the hydrothermal process effectively bind the polysilicon waste slag and chromium slag particles, ensuring that the wall tiles have good mechanical properties, with a compressive strength of up to 18 MPa, a water absorption rate of less than 10%, and a softening coefficient of up to 1.0, meeting the MU15 grade wall tile standard in the national standard JC / T422-2007.

[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0034] 1. Specific embodiments of the building material and preparation method thereof of the present invention are as follows:

[0035] Example 1

[0036] The method for preparing the building material of this embodiment specifically comprises the following steps:

[0037] (1) Drying polysilicon waste slag, chromium slag and quicklime at 150° C. for 5 h respectively for standby use; wherein the polysilicon slag is composed of the following components in mass percentage: SiO 2 70%,Al 2 O 3 8%, Fe 2 O 3 5%, CaO 15% and MgO 2%; the chromium slag is the chromium slag after the chromite is produced into chromium salt products, and the chromium slag is composed of the following components in mass percentage: Al 2 O 3 20%, CaO 10%, SiO 2 5%,Fe 2 O 3 30%,Cr 2 O 3 30% and MgO 5%.

[0038] (2) The polysilicon waste slag and chromium slag dried in step (1) are respectively placed in a ball mill for ball milling for 7 hours, and then sieved through a 200-mesh sieve to obtain polysilicon waste slag powder with a particle size greater than 200 mesh and chromium slag powder with a particle size greater than 200 mesh.

[0039] (3) The quicklime dried in step (1), the polysilicon waste slag powder with a particle size greater than 200 mesh obtained in step (2), and the chromium slag powder with a particle size greater than 200 mesh are mixed evenly to obtain a mixture; the mass fraction of the quicklime in the mixture is 21%, the mass fraction of the polysilicon waste slag powder is 44%, and the mass fraction of the chromium slag powder is 35%; the molar ratio of Ca / Si in the mixture is 1.02:1.

[0040] (4) The mixture obtained in step (4) was placed in a microwave digestion apparatus, pure water was added, and the solid-liquid ratio was 1:25. The temperature was raised to 210° C., and the synthesis reaction was carried out at this temperature for 1 hour. During the reaction, the pressure in the microwave digestion apparatus was 0.8 MPa. After the reaction was completed, the mixture was cooled to room temperature to obtain a slurry.

[0041] (5) The slurry obtained in step (4) is filtered and washed, and the washed solid is vacuum dried at 60° C. for 24 h to obtain a building material. The EDS spectrum of the building material prepared in Example 1 is as follows: Figure 1 As shown ( Figure 1 Elementweight in represents the element mass fraction).

[0042] Example 2

[0043] The method for preparing the building material of this embodiment specifically comprises the following steps:

[0044] (1) Drying polysilicon waste slag, chromium slag and quicklime at 150° C. for 5 h respectively for standby use; wherein the polysilicon slag is composed of the following components in mass percentage: SiO 2 68%,Al 2 O 3 9%, Fe 2 O 3 6%, CaO 15% and MgO 2%; the chromium slag is the chromium slag after the chromite is produced into chromium salt products, and the chromium slag is composed of the following components in mass percentage: Al 2 O 3 20%, CaO 8%, SiO 2 4%,Fe 2 O 3 31%,Cr 2 O 3 32% and MgO 5%.

[0045] (2) The polysilicon waste slag and chromium slag dried in step (1) are respectively placed in a ball mill for ball milling for 6 hours, and then sieved through a 200-mesh sieve to obtain polysilicon waste slag powder with a particle size greater than 200 mesh and chromium slag powder with a particle size greater than 200 mesh.

[0046] (3) The quicklime dried in step (1), the polysilicon waste slag powder with a particle size greater than 200 mesh obtained in step (2), and the chromium slag powder with a particle size greater than 200 mesh are mixed evenly to obtain a mixture; the mass fraction of the quicklime in the mixture is 23%, the mass fraction of the polysilicon waste slag powder is 42%, and the mass fraction of the chromium slag powder is 35%; the molar ratio of Ca / Si in the mixture is 1.14:1.

[0047] (4) The mixture obtained in step (4) was placed in a microwave digestion apparatus, pure water was added, and the solid-liquid ratio was 1:24. The temperature was raised to 205° C., and the synthesis reaction was carried out at this temperature for 1 hour. During the reaction, the pressure in the microwave digestion apparatus was 0.9 MPa. After the reaction was completed, the mixture was cooled to room temperature to obtain a slurry.

[0048] (5) The slurry obtained in step (4) is filtered and washed, and the washed solid is vacuum dried at 60° C. for 24 hours to obtain a building material.

[0049] Example 3

[0050] The method for preparing the building material of this embodiment specifically comprises the following steps:

[0051] (1) Drying polysilicon waste slag, chromium slag and quicklime at 150° C. for 5 h respectively for standby use; wherein the polysilicon slag is composed of the following components in mass percentage: SiO 2 67%, Al 2 O 3 10%, Fe 2 O 3 6%, CaO 15% and MgO 2%; the chromium slag is the chromium slag after the chromite is produced into chromium salt products, and the chromium slag is composed of the following components in mass percentage: Al 2 O 3 20%, CaO10%, SiO 2 2%,Fe 2 O 3 30%,Cr 2 O 3 30% and MgO 8%.

[0052] (2) The polysilicon waste slag and chromium slag dried in step (1) are respectively placed in a ball mill for ball milling for 8 hours, and then passed through a 200-mesh sieve to obtain polysilicon waste slag powder with a particle size greater than 200 mesh and chromium slag powder with a particle size greater than 200 mesh.

[0053] (3) The quicklime dried in step (1), the polysilicon waste slag powder with a particle size greater than 200 mesh obtained in step (2), and the chromium slag powder with a particle size greater than 200 mesh are mixed evenly to obtain a mixture; the mass fraction of the quicklime in the mixture is 22%, the mass fraction of the polysilicon waste slag powder is 45%, and the mass fraction of the chromium slag powder is 33%; the molar ratio of Ca / Si in the mixture is 1.11:1.

[0054] (4) The mixture obtained in step (4) was placed in a microwave digestion apparatus, pure water was added, and the solid-liquid ratio was 1:24. The temperature was raised to 208° C., and the synthesis reaction was carried out at this temperature for 1.2 hours. During the reaction, the pressure in the microwave digestion apparatus was 0.8 MPa. After the reaction was completed, the mixture was cooled to room temperature to obtain a slurry.

[0055] (5) The slurry obtained in step (4) is filtered and washed, and the washed solid is vacuum dried at 60° C. for 24 hours to obtain a building material.

[0056] Example 4

[0057] The method for preparing the building material of this embodiment specifically comprises the following steps:

[0058] (1) Drying polysilicon waste slag, chromium slag and quicklime at 150° C. for 5 h respectively for standby use; wherein the polysilicon slag is composed of the following components in mass percentage: SiO 2 70%,Al 2 O 38%, Fe 2 O 3 5%, CaO 15% and MgO 2%; the chromium slag is the chromium slag after the chromite is produced into chromium salt products, and the chromium slag is composed of the following components in mass percentage: Al 2 O 3 20%, CaO 10%, SiO 2 5%,Fe 2 O 3 30%,Cr 2 O 3 30% and MgO 5%.

[0059] (2) The polysilicon waste slag and chromium slag dried in step (1) are respectively placed in a ball mill for ball milling for 7 hours, and then sieved through a 200-mesh sieve to obtain polysilicon waste slag powder with a particle size greater than 200 mesh and chromium slag powder with a particle size greater than 200 mesh.

[0060] (3) The quicklime dried in step (1), the polysilicon waste slag powder with a particle size greater than 200 mesh obtained in step (2), and the chromium slag powder with a particle size greater than 200 mesh are mixed evenly to obtain a mixture; the mass fraction of the quicklime in the mixture is 25%, the mass fraction of the polysilicon waste slag powder is 40%, and the mass fraction of the chromium slag powder is 35%; the molar ratio of Ca / Si in the mixture is 1.02:1.

[0061] (4) The mixture obtained in step (4) was placed in a hydrothermal reactor, pure water was added, the solid-liquid ratio was 1:25, the temperature was raised to 230° C., and the synthesis reaction was carried out at this temperature for 10 hours. During the reaction, the pressure in the hydrothermal reactor was 1 MPa. After the reaction was completed, it was cooled to room temperature to obtain a slurry.

[0062] (5) The slurry obtained in step (4) is filtered and washed, and the washed solid is vacuum dried at 60° C. for 24 hours to obtain a building material.

[0063] In other embodiments, the solid-liquid ratio in step (4) is 1:22, or the temperature of the hydrothermal reaction in step (4) is 200°C, or the pressure of the hydrothermal reaction is 0.7 MPa, or the mass fraction of the polycrystalline silicon waste slag powder in the mixture of step (3) is 45%, the mass fraction of the chromium slag powder is 35%, and the mass fraction of quicklime is 20%, or the mass fraction of the polycrystalline silicon waste slag powder in the mixture of step (3) is 45%, the mass fraction of the chromium slag powder is 30%, and the mass fraction of quicklime is 25%.

[0064] 2. Specific examples of the application of the building material of the present invention in the preparation of wall tiles are as follows:

[0065] The building materials of Examples 1-4 are used to prepare wall tiles. The specific preparation method of the wall tiles is as follows: cement and building materials are placed in a mixer and mixed with water; the materials after mixing in the mixer are transported to a mold and pressed by a special brick press into a masonry with a length of 250 mm, a width of 110 mm and a height of 50 mm, and the masonry is naturally dried to obtain the wall tiles. The mass ratio of cement, water and building materials is 1:1:3.5.

[0066] Experimental Example 1

[0067] In order to investigate the performance difference between the wall bricks prepared by the building materials of the present invention and the wall bricks prepared by the conventional tobermorite building materials, conventional tobermorite building materials were used to prepare wall bricks according to the preparation method of wall bricks in the above text, and then the compressive strength, water absorption rate, softening coefficient and standard grade of wall bricks prepared by the building materials of the present invention and the wall bricks prepared by the conventional tobermorite building materials were tested, and the test results are shown in Table 1. Among them, the test standards for compressive strength, water absorption rate and softening coefficient are GB / T 4100-2015 "Ceramic Brick", GB / T 4100-2015 "Ceramic Brick" and GB / T 21144-2007 Concrete Solid Brick, respectively, and the standard grade of wall bricks is evaluated according to the national standard JC / T422-2007.

[0068] Table 1 Compressive strength, water absorption, softening coefficient and standard grade of wall bricks made of different building materials

[0069] Building Materials Compressive strength Water absorption Softening coefficient Standard Grades of Wall Tiles Example 1 18MPa 8.8% 1.0 MU15 Example 2 19MPa 8.6% 0.95 MU15 Example 3 20MPa 8.5% 0.97 MU15 Example 4 16MPa 8.9% 0.99 MU15 Conventional Tobermorite 16MPa 9.1% 0.96 MU15

[0070] Experimental Example 2

[0071] Referring to HJ5572010 "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method", the chromium slag in Example 1 and the building materials (containing chromium tobermorite) prepared in Examples 1-4 were selected for leaching experiments. The leaching experiments used the horizontal oscillation method with pure water as the leaching agent. The heavy metal solidification effect evaluation reference standard GB 5085.3-2007 "Hazardous Waste Identification Standard Leaching Toxicity Identification". The chromium leaching concentration in the chromium slag and chromium-containing tobermorite was determined by inductively coupled plasma emission spectrometry (ICP-OES). The experimental results showed that the chromium leaching concentration of the chromium slag in Example 1 was 10.63 mg / L, and the chromium leaching concentration of the building materials prepared in Examples 1-4 was shown in Table 2. Finally, the ratio of the amount of chromium not leached in the building material to the total amount of chromium in the building material was calculated to obtain the solidification rate. The solidification rates of the building materials prepared in Examples 1-4 are shown in Table 2.

[0072] Table 2 Chromium leaching concentration and curing rate of building materials prepared in Examples 1-4

[0073] Building Materials Leaching concentration (mg / L) Curing rate / % Example 1 0.152 97.74 Example 2 0.147 98.25 Example 3 0.142 98.36 Example 4 0.161 96.69

[0074] It can be seen from Table 2 that the chromium leaching concentration of the building materials prepared in Examples 1-4 is much lower than the limit value (15 mg / L) in GB5085.3-2007.

Claims

1. A method for preparing a building material, characterized in that: The following steps are involved: A mixture consisting of polysilicon waste slag powder, chromium slag powder and quicklime is subjected to hydrothermal reaction in water; in the mixture, the molar ratio of calcium element to silicon element is (1.0-1.15):

1.

2. The method for preparing the building material according to claim 1, characterized in that: The polysilicon waste slag powder is composed of the following components in mass fractions: 65% to 70% of SiO2, 8% to 10% of Al2O3, 4% to 6% of Fe2O3, 10% to 15% of CaO and 1% to 2% of MgO.

3. The method for preparing the building material according to claim 1, characterized in that: The chromium slag powder is composed of the following components in mass fractions: 20% to 25% of Al2O3, 5% to 10% of CaO, 2% to 5% of SiO2, 30% to 35% of Fe2O3, 30% to 35% of Cr2O3 and 5% to 8% of MgO.

4. The method for preparing the building material according to claim 1, characterized in that: In the mixture, the mass fraction of polysilicon waste slag powder is 40-45%, the mass fraction of chromium slag powder is 30-35%, and the mass fraction of quicklime is 20-25%.

5. The method for preparing the building material according to any one of claims 1 to 4, characterized in that: The temperature of the hydrothermal reaction is 200-230° C., the time is 1-10 hours, and the pressure is 0.7-1.0 MPa; the mass ratio of the mixture to water is 1:(22-25).

6. The method for preparing the building material according to claim 5, characterized in that: The temperature of the hydrothermal reaction is 205-230° C., the time is 1-10 hours, and the pressure is 0.8-1.0 MPa; the mass ratio of the mixture to water is 1:(24-25).

7. The method for preparing the building material according to any one of claims 1 to 4, characterized in that: The particle size of the polysilicon waste slag powder is greater than 200 mesh; the particle size of the chromium slag powder is greater than 200 mesh.

8. The method for preparing the building material according to any one of claims 1 to 4, characterized in that: In the mixture, the molar ratio of calcium element to silicon element is (1.02-1.14):1; in the mixture, the mass fraction of polysilicon waste slag powder is 40-45%, the mass fraction of chromium slag powder is 33-35%, and the mass fraction of quicklime is 21-25%; the polysilicon waste slag powder is composed of the following components in mass fractions: 67%-70% SiO2, 8%-10% Al2O3, 5%-6% Fe2O3, 15% CaO and 2% MgO; the chromium slag powder is composed of the following components in mass fractions: 20% Al2O3, 8%-10% CaO, 2%-5% SiO2, 30%-31% Fe2O3, 30%-32% Cr2O3 and 5%-8% MgO.

9. A building material prepared by the method for preparing a building material according to any one of claims 1 to 8.

10. Use of the building material according to claim 9 in preparing wall tiles.